Global financial cycles since 1880 - Galina Potjagailo; Maik H. Wolters (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2019)
The authors analyze cyclical co-movement in credit, house prices, equity prices, and long-term interest rates across 17 advanced economies. Using a time-varying multi-level dynamic factor model and more than 130 years of data, they analyze the dynamics of co-movement and compare recent developments to earlier episodes such as the early era of financial globalization from 1880 to 1913 and the Great Depression. They find that joint global dynamics across various financial quantities and prices as well as variable-specific global co-movements are important to explain fluctuations in the data. From a historical perspective, global co-movement in financial variables is not a new phenomenon. For equity prices, however, global cycles play currently a historically unprecedented role, explaining more than half of the fluctuations in the data. Global cycles in credit and housing have become much more pronounced and longer, but their importance in explaining dynamics has only increased for some economies including the US, the UK and Nordic European countries. Regarding GDP, the authors also find an increasing role for a global business cycle.
urn:nbn:de:hebis:30:3-500567
Keywords: C32; C38; E44; F44; F65; G15; N10; N20; 330; financial cycles; financial crisis; global co-movement; dynamic factor models; time-varying parameters; macro-finance